A major practicum report at Motherland Food products in Balungis, Balulang, Cagayan de Oro City - Bollo, Christine Tulen (2007)
The plant practice was conducted at Motherland Food Products in Balungis, Balulang, Cagayan de Oro during the period of April 5 to May 7, 2005. For 288 hours, the proponent was exposed in the manufacture of fruit puree, fruit premix, and juices as flavor for ice cream, baked products, jams and jellies. She was directly involved in the dispensing of raw materials and had observed the different processing procedure of frozen fruit products in production area. She also conducted some laboratory analyses in the Quality Assurance laboratory with the guidance of the Quality Assurance Personnel for the quality assessment of the finished goods. Also, she was able to apply the principles linking the operations of different equipment and had obtained several information about the company and the products manufactured. All the activities done inside and outside the company provided interpersonal relations with the workers and head of the company